Internalisasi Konsep Burhani dalam Pembelajaran: Strategi peningkatan Nalar Kritis Siswa - Mulasi, Syibran; Rijal, Syamsul; Aiyub, Aiyub; Rahmati, Rahmati; Kaharuddin, Kaharuddin (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
Current education shows that students' critical thinking skills are often underdeveloped due to learning approaches that focus more on knowledge transfer than exploration and problem solving. Burhani epistemology, which emphasises rational and analytical thinking, offers an alternative approach that can improve students'ccritical thinking skills. This study aims to examine how the internalisation of burhani epistemology in learning can improve students' critical thinking skills. The research method used is a qualitative approach with the method of documentation study and literature analysis. The research was conducted by analysing literature review and document analysis of teaching materials. Qualitative data was analysed using thematic analysis techniques. The results showed that the internalisation of burhani epistemology in learning improves students' critical thinking skills. Through the implementation of the burhani concept will have a positive impact on the development of students' reasoning power, learning that involves rational and examination of a problem, the function of reason will automatically be wide open. Through the concept of burhani reasoning, thinking and study are carried out comprehensively on the verses of the Qur'an, of course it can minimise the occurrence of blind taklid to religious teachings, for that learning through the burhani concept will give students more freedom in making discoveries and giving birth to new theories in learning activities. The results of the study confirm that the internalisation of burhani epistemology in learning can have a positive impact on the development of students' critical thinking skills. Recommendations for wider application of this concept as well as training for teachers in the burhani method are suggested to improve the quality of education and maximise students' intellectual potential.